Development of Interactive E-Workbook Based on Peer-Led Team Learning on Collaboration Skills and Critical Thinking in Basic Chemistry Concept - Ayu Rahayu; Edi Ilimu; Musdalifatul Adewia (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
Many students struggle to understand chemistry because it is abstract, conceptual, and involves numerous mathematical operations. Collaboration skills are needed for students to develop collaborative and critical thinking as part of 21st century life skills. This study aims to develop an interactive e-workbook based on PLTL (Peer-Led Team Learning) that meets the criteria of being valid, practical, and effective against collaboration and critical thinking skills. This research is an ADDIE-based development research with analysis, design, development, implementation, and evaluation stages. Limited trials were conducted on students in basic chemistry classes. The validation results show that e-workbook is valid, practical, and effective. The results of limited trial showed that collaboration skills improved in the good category with average score is 75%, and critical thinking skills improved in the medium category with average score is 0.33. It shows that the interactive e-workbook based on the PLTL model can improve collaboration and critical thinking skills and can be used to solve problems in group discussions with the help of an expert leader.